Student Worksheets Construction Training On Experimental Learning Methods Based On Basic Science Process Skills In Elementary School - Lili Chrisnawati; Dzul Fithria Mumtazah; Fadhilah Khairani (Universitas Serang Raya, 2022)
Science learning at the elementary school level must emphasize learning experiences that can train students' basic science process skills. The teacher as a facilitator is required to be able to create science learning that can practice these skills. Therefore, this training aims to train teachers to make student worksheets (LKS) that can stimulate students' basic science process skills with the experimental learning method. Participants are elementary school teachers at al-Karim Lampung. Based on the results of preliminary observations through the pretest, it is known that teachers' prior knowledge of science process skills and experimental learning at the primary school level is still low. A total of 46.15% of participants answered with an accuracy ≤ of 50%. Pretests are carried out through the Quizizz platform which aims to encourage teachers to utilize technology in learning. The training was carried out by lecturing on the importance of training students' science process skills and making worksheets based on basic science process skills in the experimental learning method. The results of the evaluation show that the participants are motivated to create learning based on students' science process skills.